The Effect of Probiotic Bacteria on Enhancing Immune Response and Reducing Pathogenic Infections - Hussein, Ali Abbas; Hussein, Kazim Miran Aabdul; Dwych, Khudhur Zayar Kumbar; Basheer Dahham, Leqaa Kareem (American Journal of Biology and Natural Sciences, 2025)
Probiotic bacteria raise host resistance to viral pathogens through induction of both innate and acquired immunity and lessen the incidence and severity of bacterial infections of the gastrointestinal and respiratory tracts. Channels used by probiotic bacteria to enhance immune response include stimulation of phagocytic activity by neutrophils, induction of regulated levels of reactive oxygen species via activation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complexes, mediation of the production of inflammatory cytokines, and restoration of intestinal microbiota following viral infections. Additional mechanisms of competitive exclusion by cell surface proteins, antimicrobial metabolite secretion, and stimulation of mucin secretion decrease the ability of pathogens to colonize the host, limiting the proliferation of gastrointestinal and respiratory pathogens. Probiotics are living microorganisms capable of establishing a beneficial host-microbial relationship following ingestion. Probiotics exhibit promising effects in the prevention of gastrointestinal and respiratory tract infections. Administration of probiotics from genera Lactobacillus and Bifidobacterium increases innate immune responses to pathogen-associated molecular patterns and signaling through toll-like receptors, stimulating phagocytic and cytolytic activity and increasing pathogen clearance. Probiotic administration increases the production of mucosal immunoglobulin A (IgA) in imperative mucosal sites such as the intestine, respiratory tract, and vagina, assisting in the clearance of foreign pathogens. Probiotic strains from genera Lactobacillus and Bifidobacterium promote appropriate regulation of the adaptive immune response to infection via mechanisms dependent on antigen-presenting cells of the mucosal immune system and cytokine production by dendritic cells and T cells. Studies from randomized controlled trials and meta-analyses indicate that specific probiotic bacteria can reduce the number of symptoms associated with common acute respiratory infections in a strain-specific manner and reduce the incidence of common acute diarrheal diseases when maintained at sufficient numbers for an appropriate duration.